Caveolin-3 Promotes a Vascular Smooth Muscle Contractile Phenotype - Gutierrez-Pajares, Jorge L.; Iturrieta, Jeannette; Dulam, Vipin; Wang, Yu; Pavlides, Stephanos; Malacari, Gabriella; Lisanti, Michael P.; Frank, Philippe G. (Frontiers in Cardiovascular Medicine, 2015)
Epidemiological studies have demonstrated the importance of cardiovascular diseases in Western countries. Among the cell types associated with a dysfunctional vasculature, smooth muscle cells are believed to play an essential role in the development of these illnesses. Vascular smooth muscle cells are key regulators of the vascular tone and also have an important function in the development of atherosclerosis and restenosis. While in the normal vasculature contractile smooth muscle cells are predominant, in atherosclerotic vascular lesions, synthetic cells migrate toward the neointima, proliferate, and synthetize extracellular matrix proteins. In the present study, we have examined the role of caveolin-3 in the regulation of smooth muscle cell phenotype. Caveolin-3 is expressed in vivo in normal arterial smooth muscle cells, but its expression appears to be lost in cultured smooth muscle cells. Our data show that caveolin-3 expression in the A7r5 smooth muscle cell line is associated with increased expression of contractility markers such as smooth muscle  actin, smooth muscle myosin heavy chain but decreased expression of the synthetic phenotype markers such as p-Elk and Klf4. Moreover, we also show that caveolin-3 expression can reduce proliferation upon treatment with LDL or PDGF. Finally, we show that caveolin-3-expressing smooth muscle cells are less sensitive to apoptosis than control cells upon treatment with oxidized LDL. Taken together, our data suggest that caveolin-3 can regulate the phenotypic switch between contractile and synthetic smooth muscle cells. A better understanding of the factors regulating caveolin-3 expression and function in this cell type will permit the development of a better comprehension of the factors regulating smooth muscle function in atherosclerosis and restenosis.